Paleoproterozoic formation age for the Siberian cratonic mantle: Hf and Nd isotope data on refractory peridotite xenoliths from the Udachnaya kimberlite - Doucet, Luc-Serge; Ionov, D.; Golovin, A. (Elsevier Science BV, 2015)
© 2014 Elsevier B.V. The formation age of the Siberian cratonic mantle is not well established as yet. Re-Os data on various mantle-derived materials have shown that it contains Archaean components, but the reported Re-depletion ages show a broad variation range (3.4 to 1Ga) and are commonly =2Ga for peridotite xenoliths. We report Hf and Nd isotope data for cpx and garnet separated from nine refractory spinel and garnet peridotite xenoliths from the Udachnaya kimberlite. The cpx from low-opx spinel harzburgites show extremely high eHf values, from +607 to +2084, which testify to long-term evolution of these rocks with high Lu/Hf ratios, consistent with their residual origin and near absence of post-melting enrichments in the Lu-Hf system. Such high eHf values are unusual for cpx from other cratonic peridotites and are higher than those reported for depleted cpx in off-cratonic peridotites. The clinopyroxenes from low-opx spinel harzburgites yield Hf model ages from 1.9 to 1.7Ga while the cpx from high-opx spinel harzburgites yield Hf model ages from 3.0 to 1.9Ga. When plotted together, they define a Lu/Hf isochron with an age of 1.80Ga, which we consider as a robust estimate of the formation age (melt extraction event) because it is obtained on residual rocks that show no evidence for HREE and Hf enrichments and because the model ages for three out of four individual samples are similar to each other. The cpx have high eNd of +94 to +123, which are inconsistent with their low Sm/Nd PM of < 1 and yield no meaningful age estimates. The consistently high, positive eNd in these cpxs can be interpreted in terms of long-term evolution of refractory peridotites with high Sm/Nd, followed by relatively recent LREE enrichments.We infer that a significant part of the lithospheric mantle in the central Siberian craton may have been formed during a major event (or a series of events) at around 1.8. Ga. Older ages reported for the central Siberian craton may refer to less common materials from cratonic or other domains formed in the Archaean that were later incorporated into the cratonic roots. The transition from the "Archaean" to "modern" tectonic regimes in Siberia and possibly elsewhere may have taken place at 1.8-1.9. Ga rather than at ~. 2.5. Ga, i.e. in the second half of the Paleoproterozoic rather than at the Archaean-Proterozoic boundary, at which time the asthenospheric mantle became generally too cold to experience high-degree melting on a large scale. The ~. 1.8. Ga formation age of the Siberian cratonic mantle is coeval with that for a major part of the ancient continental crust in the central Siberian craton. The temporal crust-mantle links may be explained either by the generation of the initial source materials for continental crust in the same melting event that formed the residual peridotites or, alternatively, by subduction and melting of pre-existing proto-lithosphere destabilized by a major mantle upwelling that formed the residual mantle.